2020
DOI: 10.19139/soic-2310-5070-902
|View full text |Cite
|
Sign up to set email alerts
|

GMM Estimation of Continuous-Time Bilinear Processes

Abstract: This paper examines the moments properties in frequency domain of the class of …first order continuous-timebilinear processes (COBL(1,1) for short) with time-varying (resp. time-invariant) coefficients. So, we used theassociated evolutionary (or time-varying) transfer functions to study the structure of second-order of the process and its powers. In particular, for time-invariant case, an expression of the moments of any order are showed and the continuous-time AR (CAR) representation of COBL(1,1) is given as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Demonstrating the theorem's applicability with the proposed models, it is revealed that this particular set of models yields highly accurate coefficient estimates, contingent upon stability conditions. This underscores their efficacy in practical applications requiring robust estimation methodologies [14,15].…”
Section: Comments and Main Resultsmentioning
confidence: 90%
“…Demonstrating the theorem's applicability with the proposed models, it is revealed that this particular set of models yields highly accurate coefficient estimates, contingent upon stability conditions. This underscores their efficacy in practical applications requiring robust estimation methodologies [14,15].…”
Section: Comments and Main Resultsmentioning
confidence: 90%